The Effect of Inflation and Exchange Rates on Stock Prices in Banking Sub-Sector Companies Listed on The Indonesian Stock Exchange - Uswatun Hasanah; Muhammad Kurniawan; Edduar Hendri (Riset Akuntansi dan Bisnis Indonesia, 2025)
Purpose:. This study aims to determine the influence of inflation variables and exchange rates on share prices. Research/methodology: This quantitative study examined 15 of 47 banking companies listed on the IDX (2019–2023), using 75 financial reports. Data were analyzed through classical assumption tests, determination coefficients, and hypothesis testing using t and F tests. Results: The results show that both inflation and exchange rates have a significant partial effect on banking share prices (sig. 0.000 < 0.05), and together they also significantly influence share prices during 2019–2023. Conlusions: Inflation and exchange rates significantly affect banking stock prices on the IDX (2019–2023), indicating that macroeconomic stability strongly influences market performance and investor confidence. Limitations: The object of the research is only banking sub-sector companies listed on the Indonesia Stock Exchange for the 2019–2023 period and only includes inflation, exchange rates, and stock prices Contribution: This research aims to contribute to science at the Faculty of Economics and Business, provide reading materials in the library of the University of PGRI Palembang about inflation and exchange rates on the stock prices of companies in the banking sub-sector on the Indonesia Stock Exchange for the 2019-2023 period, and increase the company's insight into the development of stock prices related to inflation and exchange rates.